2005
DOI: 10.1007/s10705-005-0073-5
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Uptake and Balance of Cotton + Pigeonpea Strip Intercropping on Rainfed Vertisols of Central India

Abstract: Nutrient uptake and balance of the cotton (Gossypium hirsutum L.) + pigeonpea (Cajanus cajan(L.) Millsp.), a traditional strip intercropping system practiced on the rainfed Vertisols of central India is not known to us. On-farm participatory trials were conducted on 10 farmer fields, five each on medium deep (MDS) and deep soils (DS) of Nagpur, central India to determine the effect of technological interventions on N, P and K uptake of cotton and pigeonpea. The nutrient balance was also quantified as a differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 13 publications
2
16
0
Order By: Relevance
“…This might have increased photosynthetic activities of plant which ultimately helped to realized greater biomass accumulation (Singh and Ahlawat 2014a). Our results are in general agreement with other studies in which higher productivity and energy returns were largely associated with combined application of organic and inorganic sources of N (Blaise et al 2005). The 100 % RDN application through urea maintained the highest energy intensiveness (Table 9) due to less cost of cultivation and energy input in comparison to FYM treatments (Singh et al 1997).…”
Section: Discussionsupporting
confidence: 92%
“…This might have increased photosynthetic activities of plant which ultimately helped to realized greater biomass accumulation (Singh and Ahlawat 2014a). Our results are in general agreement with other studies in which higher productivity and energy returns were largely associated with combined application of organic and inorganic sources of N (Blaise et al 2005). The 100 % RDN application through urea maintained the highest energy intensiveness (Table 9) due to less cost of cultivation and energy input in comparison to FYM treatments (Singh et al 1997).…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, K acquisition averaged over the intercropping systems was 299 kg ha −1 and 45.5 kg ha −1 higher than by the monocultures in 2012. Our results are consistent with several published studies (Blaise et al 2005;Mondal et al 2004). This implies that K fertilizer or manure applications are potentially important in both intercropping and rotational cropping systems.…”
Section: Continuous Intercropping Maintains Soil Fertility In Terms Osupporting
confidence: 94%
“…Still, even though the intercropping system as a whole may consume more nitrogen, each component crop in an intercropping system is likely to take up less nitrogen than in a monocrop situation, due to competition with the other crop. This, for instance, was found by Blaise et al (2005), who reported that total N uptake in strip intercropping of cotton and pigeon pea in rainfed regions of central India was lower than in sole cotton because of a lower crop productivity.…”
Section: Introductionmentioning
confidence: 60%